Učinek treninga prostih metov z zmanjšanim obročem pri mladih košarkarjih - Trafela, Anže (Šport (Ljubljana), 2017)
Although it is an important factor of the playing performance in basketball, the free-throw training usually receives little attention. Therefore, it is not surprising that basketball players with a relatively poor free-throw technique and low performance can be found even at the top competitive level. The aim of this study is to analyse the effectiveness of the training of throwing at the basket with a reduced hoop diameter on a sample of 11 young basketball players. Contrary to the findings of some other authors, training with a special basket with a reduced hoop diameter has not proven to be effective. In the period of ten weeks, when a special free-throw training programme was implemented, the performance of free throws did not improve and the angle of incidence of the ball at the basket did not increase as a result of the reduced hoop diameter. It seems that reduced hoop diameter is a disturbing factor for some players, as they find it difficult to adapt to. In our opinion the use of a smaller hoop is reasonable only for those basketball players who have a distinctively low throw parable and are thus less successful when performing free throws.
Keywords: angle of incidence; basketball; košarka; met; performance; sport; šport; throw; trening; uspešnost; vpadni kot